Classroom Management Challenges Encountered by Elementary Public School Teachers in Inclusive Classrooms - Chavez, Stephanie; Ramos, Menchie; Tactac, Ma. Daisy; Paguigan, Jesus (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the classroom management challenges encountered by elementary teachers in Saluysoy Integrated School in inclusive classrooms. Specifically, it focused on challenges related to learner behavior, classroom discipline, learner participation, time management, and teacher preparedness. The study was anchored on Universal Design for Learning, proactive classroom management, and the Input-Process-Output model. A descriptive quantitative research design was used, with elementary teachers handling inclusive classrooms as respondents. The study employed purposive sampling and used a survey questionnaire composed of items on demographic profile and classroom management challenges. Data were analyzed using frequency and percentage, weighted mean, and ranking. Results showed that teachers strongly agreed that classroom management challenges were present in inclusive classrooms, with an overall weighted mean of 4.30. Managing disruptive behavior obtained the highest weighted mean of 4.45, followed by handling diverse learner needs with 4.40, maintaining classroom discipline with 4.30, ensuring learner participation with 4.20, and time management difficulties with 4.15. The findings indicate that inclusive classroom management requires teacher preparedness, instructional flexibility, proactive discipline, and school-based support. The study recommends seminars and workshops on inclusive education, classroom management, differentiated instruction, Universal Design for Learning, and learner participation, as well as stronger instructional support, mentoring, parent-teacher communication, and possible SPED support personnel. The study supports SDG 4, SDG 3, SDG 10, SDG 16, and SDG 17 by promoting inclusive, safe, equitable, and collaborative learning environments. Its sustainability impact lies in strengthening educational, institutional, social, and community-based support systems for inclusive education.
Keywords: Classroom Discipline; Classroom Management; Inclusive Classrooms; Inclusive Education; Learner Behavior; Learner Participation; Teacher Preparedness